Information Slices: Visualising and Exploring Large Hierarchies using Cascading, Semi-Circular Discs - Andrews, Keith; Heidegger, Helmut
This paper presents work in progress on a new technique for visualising and manipulating large hierarchies. The information slices approach compactly visualises hierarchical structures using a series of semi-circular discs. The technique is described in the context of our early experience with a prototype file system visualiser based on information slices.